2011
DOI: 10.1063/1.3669425
|View full text |Cite
|
Sign up to set email alerts
|

Guided ion beam and theoretical study of the reactions of Os+ with H2, D2, and HD

Abstract: Reactions of the third-row transition metal cation Os(+) with H(2), D(2), and HD to form OsH(+) (OsD(+)) were studied using a guided ion beam tandem mass spectrometer. A flow tube ion source produces Os(+) in its (6)D (6s(1)5d(6)) electronic ground state level. Corresponding state-specific reaction cross sections are obtained. The kinetic energy dependences of the cross sections for the endothermic formation of OsH(+) and OsD(+) are analyzed to give a 0 K bond dissociation energy of D(0)(Os(+)-H) = 2.45 ± 0.10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 82 publications
0
20
1
Order By: Relevance
“…22,23,25,27,28,30,53,69,70,86 In all cases, the difference is attributed to competition with the formation of the metal carbene because of a shared, common intermediate. Because reactions of M + with H 2 produce only one product, no competition exists that may delay the onset of reaction.…”
Section: Inorganic Chemistrymentioning
confidence: 92%
“…22,23,25,27,28,30,53,69,70,86 In all cases, the difference is attributed to competition with the formation of the metal carbene because of a shared, common intermediate. Because reactions of M + with H 2 produce only one product, no competition exists that may delay the onset of reaction.…”
Section: Inorganic Chemistrymentioning
confidence: 92%
“…11 On the other hand, the reactive collisions between metal ions and molecular hydrogen (M + + H 2 ) are important objects to study reaction dynamics, and a broad range of M + ions have been performed by the guide ion beam methods in combination with theoretical calculations. [12][13][14][15] The BeH 2 + system has been widely studied in the related elds of cold and ultracold chemistry. In 2006, Roth et al 2 studied the Be + ( 2 P) + H 2 / BeH + + H reaction by a laser-cooling ion trap apparatus with the millikelvin level translational temperatures of Be + ions.…”
Section: Introductionmentioning
confidence: 99%
“…Tel. : +86 10 62568330; fax: +86 10 62559373. to the reactivity of bare noble-metal atoms or related cluster species, such as Pt + [21,22], Au 2 + [23], PtAu + [24], Pd 2 + [25], and so on [26][27][28][29][30][31]. These studies have demonstrated rich structure-property relationships in bond activation of small organic and inorganic molecules by noble metals.…”
Section: Introductionmentioning
confidence: 94%